Implementation of the Principle of Justice in the Notaries Public - D. A. Semyannikova (Теоретическая и прикладная юриспруденция)
In the course of the study, it was revealed that justice in the activities of a notary is, in a narrow sense, in his impartiality, and in a broad sense, in the purpose of the institution of the notary itself and the features of the mechanisms used to implement the main goals of the notary. The main feature is its dualistic nature, on the one hand, the notary acts on behalf of the state when performing notarial actions, on the other hand, he primarily respects the private legitimate interests of the citizens and legal entities who have applied, so that legal ignorance cannot be used to their detriment. The notary acts as a kind of “buffer” and a guide between the law and the persons to whom this law applies.